RURAL PARTNERSHIP AS A GOVERNANCE MECHANISM: TOWARD AN ORGANIZATIONAL ECONOMICS PERSPECTIVE ON RURAL GOVERNANCE - Vladislav Valentinov (IAMO, 2006)
The paper develops an organizational economics approach to explaining rural governance by viewing rural partnerships as a governance mechanism that can be used for organization of rural development activities along with markets and hierarchies. Utilizing the framework of the property rights theory of the firm and transaction cost economics, it is argued that rural partnerships exhibit superior transaction cost-economizing attributes due to their ability to accommodate high commonality of interests of local actors in the sustainable development of their rural areas. This argumentation is based on the proposition to regard the commonality of transaction participants' interests, rather than transaction attributes, as a major determinant of suitability of governance mechanisms to specific transactions. The paper concludes with the discussion of limitations of partnership-based governance.
Keywords: rural partnership; rural development; governance mechanism; transaction costs; property rights; rural partnership; rural development; governance mechanism; transaction costs; property rights